Sinomenine regulates macrophage reprogramming via the PI3K-AKT-NF-κB pathway to ameliorate osteoarthritis - Linlin Zhang; Zujian Huang; Liang Yan; Yang Liu; Yaping Wan; Xianyue Shen; Wei Huang; Wendan Cheng (Tissue and Cell, 2027)

Micro/nanoscale biochar facilitates cadmium immobilization and soybean resilience: Insights from microbial life-history strategies and plant physiological response - Yaping Wang; Yichen Xu; Yini Cao; Yi Hu; Changrui Liu; Chuanxin Ma; Wende Yan (Bioresource Technology, 2026)

GLSP ameliorates monocrotaline-induced pulmonary arterial hypertension through inhibition of the PI3K/AKT and MAPK signaling pathways - Yingying Wei; Siying Zuo; Na Deng; Haijun Guo; Liwei You; Yaping Zuo; Yan Wu; Zhangrong Chen; Wei Li; Xiaoyun Si (Journal of Molecular Histology, 2026)

Effective risks and dominant factors of drought-flood abrupt alternation events to global socio-ecological systems - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng; Baisha Weng; Jianzhu Li (Journal of Hydrology, 2026)

Rapid particulate microplastics removal from stormwater: Distinct adsorption behavior and data-driven intelligent prediction - Yan Yaping; Song Xichen; Wang Xiaojuan; Liu Xiuyun; Zhou Jianqiang; Wang Gang; Zhang Tingting; Wei Bigui; Zhao Yaqian (Chemical Engineering Journal, 2026)

Deep learning-enabled real-time acoustofluidic sorting for selective microalgae recovery under wastewater-relevant heterogeneous conditions - Zihan Li; Xian Jiang; Wenzhe Gong; Aoyang Tang; Yan Ma; Xia Du; Yaping Xie; Tielin Shi; Zhiyong Liu; Guanglan Liao; Lei Nie (Bioresource Technology, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

Promoting high energy density Mn-based layered oxide cathodes via surface structural regulation for sodium-ion batteries - Maohan Liu; Lingyi Kong; Xinyu Zhang; Yaping Yan; Haiyan Hu; Hanshen Xin; Jiayang Li; Yubin Niu; Yanfang Zhu; Yao Xiao (Chemical Engineering Journal, 2026)

Controlled Maillard glycation enhances emulsifying performance of plant proteins: Insights from quinoa protein–xylose conjugates - Jinlong Yan; Xiaofang Zhou; Yaping Wang; Benu Adhikari; Wanping Zhang; Zijia Zhang (Innovative Food Science & Emerging Technologies, 2026)

Hydrogen production via gasification of corn stover photo-fermentation Residue: Catalytic mechanism of alkali metals - Kaixin Wang; Xiaoyu Yan; Yaping Zheng; Jiatao Dang; Sen Yao; Wei Wang; Panbo Yang; Shuheng Zhao; Jianjun Hu (Bioresource Technology, 2026)

Linear time-lag effects and nonlinear interactions of global drought-flood abrupt alternation in responses to multiple factors - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng; Jianzhu Li (Journal of Hydrology, 2026)

Trio-active bone scaffold with multivalent ion doping establishes an osteo–angio–immune bone regenerative axis - Jiren Yan; Xiang Li; Teng Ye; Weinan Cheng; Yaping Li; Gen Wen; Fei Zhang; Linyang Chu (Chemical Engineering Journal, 2026)

Removal performance and mechanisms of microplastics by superhydrophobic medium - Zhang Tingting; Cheng Wenqing; Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Gao Suxia; Li Hao; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

Reconstructing all-weather remotely sensed air temperature via a kernel-based temporal filling and bias correction (KTF-BC) framework - Yan Xin; Yongming Xu; Xudong Tong; Meng Ji; Yaping Mo; Yonghong Liu; Shanyou Zhu (Remote Sensing of Environment, 2026)

Synchrony of prehistoric agricultural evolution and drought events in the North China Plain - Yanpeng Li; Shengrui Li; Hai Xu; Keliang Zhao; Guanhan Chen; Yaping Zhang; Jiacheng Ma; Junchi Liu; Yong Ge; Yan Zheng; Xinying Zhou; Xiaoqiang Li (Quaternary Science Reviews, 2026)

Multi-objective Optimization of Sponge City Storage Tank Considering Inlet and Outlet Water Conditions-based on NSGA-II Algorithm - Wang Xiaojuan; Ma Yingqiang; Li Hao; Qin Jie; Xiao Yifei; Yan Yaping; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Water Resources Management, 2026)

Study on the removal and ecological risk of microplastics in road runoff by collapsible loess bioretention facilities - Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Zhang Tingting; Gao Suxia; Li Jiapeng; Liu Jianlin; Cao Lianbao; Li Wei; Wei Bigui (Process Safety and Environmental Protection, 2026)

Spatiotemporal dynamics of microplastics in urban stormwater runoff: Functional area effects and transport pathways (Shanghai, China) - Junhao Li; Bowen Yu; Chengjin Cao; Liuxing Wu; Yaping Zhao; Ruiyun Zhu; Yangyang Hu; Minsheng Huang; Lei Wang; Xinlin Yan (Journal of Contaminant Hydrology, 2026)

Quantifying glacier and snow shrinkage: future water stress in Northern Tien Shan, Central Asia - Qiudong Zhao; Yongjian Ding; Zizhen Jin; Yan Qin; Rui He; Donghui Shangguan; Shiqiang Zhang; Yaping Chang; Haidong Han (CATENA, 2026)

Life-course body shape trajectories and cerebral oxygen metabolism in community-dwelling older adults - Yifan Yan; Yaping Zhang; Xuhao Zhao; Renwei Chen; Shenghao Fang; Yi Zhou; Jingkai Huang; Fuyan Wang; Christopher Chen; Zixuan Lin; Xin Xu (GeroScience, 2026)
Obesity and lifelong body-shape fluctuation are associated with late-life structural brain damage, suggesting the involvement of metabolic pathways. The cerebral metabolic rate of oxygen (CMRO₂) reflects hemodynamic and oxidative stress and precedes structural atrophy, but its role in adiposity-related brain change remains unclear. We examined whether current and life-course adiposity relate to CMRO₂ and to structural change. A total of 303 community-dwelling adults aged 50 years and older were included. Body shape was assessed using Body Mass Index (BMI) and Body Roundness Index (BRI). Global CMRO₂ was derived from TRUST and phase-contrast MRI. T1-weighted MPRAGE provided volumetry, and medial temporal atrophy (MTA) grading. General linear models estimated associations of BMI and BRI with CMRO₂, including age interactions. Age-stratified mediation tested CMRO₂ as a mediator of adiposity to MTA associations. Body-shape trajectories at ages 25, 40, 60, and current age were modeled and related to CMRO₂ and metabolism-related regions. Adiposity was associated with lower CMRO₂: with overweight (β = -1.12 μmol/100 g/min, 95%CI = (-1.96, -0.28)) and higher BRI (β = -1.31, 95%CI = (-2.36, -0.27)) showing stronger effects with advancing age. Among participants aged 70 years, CMRO₂ mediated the association between BMI and MTA (indirect β = 0.06, 95%CI = (0.01, 0.14)). Three adulthood body-shape patterns emerged, and CMRO₂ was lower in moderate increasing (β = -11.40; 95%CI = (-20.90, -1.90)) and high-rising (β = − 12.23; 95%CI = (-23.56, -0.90)) groups. Metabolism-related regions were larger in higher-risk patterns, particularly the left hypothalamus. Greater and prolonged adiposity is linked to reduced CMRO₂ and related structural differences in older adults.

Zn isotopic composition and variability in large-scale aquatic environment of the Tibetan Plateau: implications for Zn migration and sources - Xiaoli Liu; Zhiwen Dong; Yan Yan; Rui Wu; Lunche Wang; Yaping Shao (Journal of Hydrology, 2026)

Three-dimensional discrete fracture network identification based on deep learning and reversible jump Markov chain Monte Carlo algorithm - Zhenting Sun; Lei Ma; Quan Li; Yaping Deng; Han Qiu; Haichun Ma; Cihai Chen; Yongshuai Yan; Jiazhong Qian (International Journal of Rock Mechanics and Mining Sciences, 2026)

Biogenic amines in fermented foods: A comprehensive review from formation pathways, risk analysis, detection technologies to control measures - Yaping Wang; Bing Yan; Haiqian Xu; Yanyan Huang; Qinglin Sheng; Lang-Hong Wang (Food Research International, 2026)

Deep insights into LDH reconstruction for enhanced capacitive deionization - Xiaohong Shang; Jinguo Hu; Yaping Yan; Siyu Li; Jiameng Diao; Haoyu Wang; Bin Hu; Hao Wang (Journal of Environmental Chemical Engineering, 2025)

Complete loss of 5-methyltetrahydrofolate in wheat during simulated gastric digestion - Fengyuan Liu; Jinxian Zheng; Yunfei Mo; Yaping Xiao; Yun Wang; Hua Zhang; Jing-Kun Yan; Yaqing Liu (Food Chemistry, 2025)

Unveiling the stepwise catalysis of Ni Fe bimetallic single-atom sites toward high-efficiency lithium–sulfur batteries - Yaping Yan; Yi Yang; Zhihui Zhang; Changzheng Xin; Nan Yang; Tianwei He; Shude Liu; Zixu Sun; Yusuke Yamauchi; Ling Kang (Chemical Engineering Journal, 2025)

Exploring the potential of UAV-based thermal imagery for monitoring diurnal variations in the microscale urban thermal environment - Meng Ji; Yongming Xu; Shanyou Zhu; Yang Zhang; Yan Xin; Yaping Mo (Energy and Buildings, 2025)

The dual-function of VN catalytic sites at cathode and anode toward high-performance lithium‑sulfur batteries - Yaping Yan; Yi Yang; Liu Yang; Xuefeng Luo; Guangzhao Wang; Qingquan Xue; Andreu Cabot; Hua Kun Liu; Shi Xue Dou; Zixu Sun (Chemical Engineering Journal, 2025)

A framework for the dynamic identification of drought propensity: The predictive role of energy changes in drought events - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng (Atmospheric Research, 2025)

Reuse of waste corn stalk as heavy metal adsorbent by sulfydryl modification: Optimization of adsorption performance and adsorption mechanism - Xiuyun Liu; Gang Wang; Bigui Wei; Yaping Yan; Liang Dai (Process Safety and Environmental Protection, 2025)

Environmental tobacco smoke exposure in pregnant women and thyroid hormone levels in newborn cord blood: A birth cohort in China - Tengwei Gui; Yan Li; Yaping Liu; Jirong Li; Tong Luo; Shuqi Chen; Xiaoxiao Song; Xia Xiao (Environmental Pollution, 2025)

Multifunctional MOF-based superhydrophobic quartz sand: Interfacial interactions for durable and efficient microplastic removal in stormwater - Yaping Yan; Xiuyun Liu; Xiaojuan Wang; Haiyan Wen; Gang Wang; Liang Dai; Suxia Gao; Tingting Zhang; Bigui Wei (Chemical Engineering Journal, 2025)

Determination and Application of a New Drought Resistant Control Water Level for Multi-Reservoir Systems Based on a Water Resource Allocation Model - Yaping Cheng; Ziqi Yan; Denghua Yan; Miao Liu; Ruishen Wei (Water Resources Management, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Inversion of aboveground biomass of Spartina alterniflora based on multispectral UAV - Ziyao Chen; Yan Gu; Jianchun Chen; Dingchen Liu; Junjie Rui; Shibing Zhu; Yaping Wang (Acta Oceanologica Sinica, 2025)

Polysaccharide from discarded tobacco leaves and its anti-TMV activities - Yan Wang; Zhengxuan Wang; Yaping Liu; Charles Brennan; Jueting Liu; Jinhong Zhou; Wenbing Zhou; Guiguang Cheng (Pesticide Biochemistry and Physiology, 2025)

Structural remodeling of UiO-66(Ce) into oxygen vacancy defect-rich CeO2: Enhancing selective adsorption of As(III) - Tao Zhang; Xu Tang; Jing Xing; Huan Xu; Ruyu Yan; Yaping Zhao (Journal of Hazardous Materials, 2025)

Assessing Fluoride Contamination in Groundwater of Informal Landfills in the Yangtze River Delta: Implications for Environmental Security and Sustainable Resource Management - Lichen Liang; Xiaofei Yan; Yaping Qi; Lili Wang; Haifeng Tu; Hao Jiang; Dan Wang; Houhu Zhang; Yuanshun Xu (Water, Air, & Soil Pollution, 2025)

Introducing transition metal cations to promote the oxygen reduction kinetics of double perovskite as SOFC cathode - Jie Yang; Yaping Zhang; Xiaofei Zhu; Jinghe Bai; Shangyu Li; Wenfu Yan; Defeng Zhou (Chemical Engineering Journal, 2025)

Density functional theory and machine learning method for the rapid screening of dual-atom catalysts in N2 electroreduction - Qingchen Li; Nan Xia; Yaping Zhu; Yan Gao; Yahui Liu; Haifeng Wang (Chemical Engineering Journal, 2025)

Biochar and PGPR Influence Rhizosphere Bacteria and Synergistically Regulate Tomato Seedling Biomass Under Greenhouse Conditions - Zhenlu Yan; Yuyuan Xing; Changli Ma; Xin Li; Yaping Duan; Xue Wang; Minghao Liu; Muhammad Khashi u Rahman; Xingang Zhou (Journal of Soil Science and Plant Nutrition, 2025)

The effect of removing bound polyphenols on the physicochemical and functional properties of Rosa roxburghii tratt dietary fiber in vitro - Xiaoli Zhou; Zhicheng Qin; Yan Chen; Yaping Wang; Dong Lin; Lingshuai Meng (Food Bioscience, 2025)

The diurnal variation characteristics of warm season precipitation in Chongqing from 2011 to 2021 - Yingying Zhou; Yan Zhang; Chengzhi Deng; Qu Guo; Yaping Zhang; Yi Liu; Hong Zhang; Tingting Liu; Fan Xia (Theoretical and Applied Climatology, 2025)

Stochastic modeling of discrete fracture network considering spatial pattern and variability of fracture distribution - Di Gao; Lei Ma; Jiazhong Qian; Qiankun Luo; Haichun Ma; Yaping Deng; Xiaosan Yan (Geosciences Journal, 2025)

Tankyrase inhibitor IWR-1 modulates HIPPO and Transforming Growth Factor β signaling in primed bovine embryonic stem cells cultured on mouse embryonic fibroblasts - Yao Xiao; Yujie Wang; Minghao Zhang; Yan Zhang; Zhihua Ju; Jinpeng Wang; Yaran Zhang; Chunhong Yang; Xiuge Wang; Qiang Jiang; Yaping Gao; Xiaochao Wei; et al. (Theriogenology, 2025)

Boosting electrocatalytic performance of BaPrO3-δ −based cathode catalysts by Co and Ni co-doping for protonic ceramic fuel cells - Bo Liu; Yanping Zheng; Xinwei Yang; Yaping Liu; Dong Yan; Jian Li; Lichao Jia (Chemical Engineering Journal, 2025)

Analysis of Common Genetic Variation of Anxiety Disorders in Essential Tremor - Yaping Yan; Lanxiao Cao; Luyan Gu; Congying Xu; Jinyu Lu; Dayao Lv; Jun Tian; Xinzhen Yin; Jiali Pu; Baorong Zhang; Guohua Zhao (Journal of Molecular Neuroscience, 2025)

Development of the CMA-ChemRA: China Regional Weakly Coupled Chemical-Weather Reanalysis System with product since 2007 - Tao Zhang; Zijiang Zhou; Zhisen Zhang; Junting Zhong; Zhiquan Liu; Xiaoye Zhang; Wenhui Xu; Lipeng Jiang; Jie Liao; Yaping Ma; Yike Zhou; Huiying Wang; et al. (Science of The Total Environment, 2024)

Occurrence and distribution of atrazine in groundwater from agricultural areas in China - Shengpin Li; Fuyang Huang; Haitao Piao; Wenpeng Li; Fei Liu; Qianying Zhu; Yaping He; Jialin Wang; Maohua Yan (Science of The Total Environment, 2024)

Effective identification of debris-covered glaciers in Western China using multiple machine-learning algorithms - Rui He; Donghui Shangguan; Qiudong Zhao; Shiqiang Zhang; Zizhen Jin; Yan Qin; Yaping Chang (Science of The Total Environment, 2024)

Removal performance for copper and turbidity with dithiocarboxyl aminomethy-polyacrylamide as flocculant - Yaping Yan; Gang Wang; Bigui Wei; Xin Wang (Journal of Water Process Engineering, 2024)

One-step synthesis of iron and carbon-quantum-dot co-decorated graphitic carbon nitride photocatalysts for carbamazepine degradation - Xiaoli Liu; Yaping Wang; Yutao Xie; Tiefeng Xu; Yan Gu; Wangyang Lu (Journal of Environmental Chemical Engineering, 2024)

Early-onset familial essential tremor is associated with nucleotide expansions of spinocerebellar ataxia in China - Zhilin Zheng; Zeyu Zhu; Jiali Pu; Chen Zhou; Lanxiao Cao; Dayao Lv; Jinyu Lu; Gaohua Zhao; Yanxing Chen; Jun Tian; Xinzhen Yin; Baorong Zhang; et al. (Molecular Biology Reports, 2024)

One-step hydrothermal synthesis of nitrogen-doped carbon-quantum-dots for detection and efficient removal of high-concentrations nicotine from tobacco wastewater under visible light - Xiaoli Liu; Yaping Wang; Yan Gu; Wangyang Lu (Chemical Engineering Journal, 2024)

Release of bound phenol from Rosa roxburghii pomace via solid-state fermentation with Trichoderma viride: Mechanisms of change - Yanli Wang; Yaping Wang; Xiaoli Zhou; Bin Du; Yan Chen (Food Bioscience, 2024)

Deep eutectic solvent microemulsions with abundant hydrogen ions in supercritical CO2 for decontamination of radioactive solid waste: Overcoming roadblocks to hydrogen ions deficiency - Huitao Lv; Jianzhang Gao; Jiaqi Chen; Tianyu Li; Chao Peng; Yaping Li; Fuqiu Ma; Yun Xue; Yongde Yan; Emmanuel Osei Tutu (Chemical Engineering Journal, 2024)

Evaluating warming trend over the tibetan plateau based on remotely sensed air temperature from 2001 to 2020 - Yan Xin; Yongming Xu; Xudong Tong; Yaping Mo; Yonghong Liu; Shanyou Zhu (Climatic Change, 2024)

Cardiac toxicity of brentuximab vedotin: a real-word disproportionality analysis of the FDA Adverse Event Reporting System (FAERS) database - Chengjie Ke; Maohua Chen; Yaping Huang; Yan Chen; Cuihong Lin; Pinfang Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Spartina alterniflora invasion benefits blue carbon sequestration in China - Jingfan Zhang; Dehua Mao; Jihua Liu; Yaping Chen; Matthew Kirwan; Christian Sanders; Jinge Zhou; Zhe Lu; Guoming Qin; Xingyun Huang; Hui Li; Hengqi Yan; et al. (Science Bulletin, 2024)

Research on the spatiotemporal evolution and influencing factors of urbanization and carbon emission efficiency coupling coordination: From the perspective of global countries - Dalai Ma; Yin Yan; Yaping Xiao; Fengtai Zhang; Haoran Zha; Ruonan Chang; Jiawei Zhang; Zuman Guo; Bitan An (Journal of Environmental Management, 2024)

Flexible and wearable functional materials for ionizing radiation Protection: A perspective review - Hao Li; Linping Yan; Jibo Zhou; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2024)

An Advanced Molecularly Imprinted Photochemical Sensor Based Carbon Quantum dots for Highly Sensitive Detection of Chloramphenicol in Food - Hao Liu; Jing Yang; Xuyuan Sun; Peijie Wu; Guan Wang; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Efficient biostimulation of microbial dechlorination of polychlorinated biphenyls by acetate and lactate under nitrate reducing conditions: Insights into dechlorination pathways and functional genes - Yan Xu; Ying Wang; An Zheng; Yaping Yuan; Lei Xu; Yanqiang Tang; Qingdong Qin (Journal of Hazardous Materials, 2024)

On-site smartphone detection of ethanol content using paper-based colorimetric polydiacetylene sensor arrays - Dong-En Wang; Changhan Yan; Sirui Bai; Yaping Zhang; Wenjing Huo; Kaiting Ning; Lei Zhao; Hui Yang; Huiyun Xu (Chemical Engineering Journal, 2024)

PSAT1 promotes autophagy to resist insufficient autophagy caused by cigarette smoke extract in human airway epithelial cells - Lixing Wang; Furong Yan; Yongbin Shi; Xiaoshan Su; Yaping Zhang (Toxicology in Vitro, 2024)

Study on the effect of cyclic catalytic pyrolysis on sludge pyrolysis products - Yan Wu; Yuexin Zhang; Maoqing Wang; Yaping Xia; Guoxin Lan; Bin Yan; Yue Yu; Xinyi Xiong; Junhan Zou; Yin Zhu (Journal of Environmental Chemical Engineering, 2024)

Probiotic Potential of Bacillus amyloliquefaciens Isolated from Tibetan Yaks - Yuanyuan He; Feiran Li; Wenqian Zhang; Miao An; Aoyun Li; Yaping Wang; Yan Zhang; Muhammad Fakhar-e-Alam Kulyar; Mudassar Iqbal; Jiakui Li (Probiotics and Antimicrobial Proteins, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Quaternary stratigraphic architecture of the Pearl River Mouth continental shelf, northern South China Sea: Unraveling stratigraphic imprints of tectonism, paleoceanography, and climate change - Haiteng Zhuo; Xin Nie; Ming Su; Wei Zhou; Yaping Lei; Yingmin Wang; Xuechao Peng; Yan Qiu; Weiyao Yan; Li'e Lin (Sedimentary Geology, 2024)

Does biogas industrial policy promote the industrial transformation? - Erga Luo; Ru Yan; Yaping He; Zhen Han; Yiyu Feng; Wenrong Qian; Jinkai Li (Resources Policy, 2024)

Efficient degradation of methylene blue by FeS2/MoS2 in heterogeneous Fenton-like process - Pengfei Yan; Haojian Wang; Mingwen Wang; Chengwen Chai; Yaping Ye (Journal of Water Process Engineering, 2023)

Tea polyphenols coated sodium alginate-gelatin 3D edible scaffold for cultured meat - Xiaohong Chen; Linzi Li; Lin Chen; Wei Shao; Yan Chen; Xiaojing Fan; Yaping Liu; Changbo Tang; Shijie Ding; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Apple trees can extract soil water from both deep layers and neighboring cropland in the tableland region of Chinese Loess Plateau - Yaping Wang; Xiaoyang Han; Weiming Yan; Liping Cheng; Xingdong Dang; Wenzhao Liu (CATENA, 2023)

Impact of the producer services agglomeration on PM2.5: A case study of the Yellow River Basin, China - Yan Liu; Yu Cheng; Ruijing Zheng; Huaxue Zhao; Yaping Wang (Journal of Geographical Sciences, 2023)

Comparison of gap-filling methods for producing all-weather daily remotely sensed near-surface air temperature - Yaping Mo; Yongming Xu; Yonghong Liu; Yan Xin; Shanyou Zhu (Remote Sensing of Environment, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Putrescine (1,4-Diaminobutane) enhances antifungal activity in postharvest mango fruit against Colletotrichum gloeosporioides through direct fungicidal and induced resistance mechanisms - Yaping Song; Yanfang Ren; Yuhao Xue; Dandan Lu; Tengyu Yan; Junyu He (Pesticide Biochemistry and Physiology, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Acceleration of Fe3+/Fe2+ cycle in garland-like MIL-101(Fe)/MoS2 nanosheets to promote peroxymonosulfate activation for sulfamethoxazole degradation - Ke Zhu; Wenlei Qin; Yaping Gan; Yizhe Huang; Zhiwei Jiang; Yuwen Chen; Xin Li; Kai Yan (Chemical Engineering Journal, 2023)

Dual recognition elements for selective determination of progesterone based on molecularly imprinted electrochemical aptasensor - Yan Huang; Daixin Ye; Jing Yang; Wenyi Zhu; Li Li; Yaping Ding (Analytica Chimica Acta, 2023)

Mettl3-mediated transcriptome-wide m6A methylation induced by cigarette smoking in human bronchial epithelial cells - Yaping Zhang; Lixing Wang; Yifei Liu; Furong Yan (Toxicology in Vitro, 2023)

Barbican-inspired bimetallic core–shell nanoparticles for fabricating natural leather-based radiation protective materials with enhanced X-ray shielding capability - Hao Li; Jibo Zhou; Linping Yan; Rui Zhong; Yaping Wang; Xuepin Liao; Bi Shi (Chemical Engineering Journal, 2023)

Long-term manuring enhances soil gross nitrogen mineralization and ammonium immobilization in subtropical area - Jun Wang; Lei Wu; Qiong Xiao; Yaping Huang; Kailou Liu; Yan Wu; Dongchu Li; Yinghua Duan; Wenju Zhang (Agriculture, Ecosystems & Environment, 2023)

Association Analysis of 27 Single Nucleotide Polymorphisms in a Chinese Population with Essential Tremor - Lanxiao Cao; Luyan Gu; Jiali Pu; Dayao Lv; Jun Tian; Xinzhen Yin; Ting Gao; Zhe Song; Jinyu Lu; Gaohua Zhao; Baorong Zhang; Yaping Yan; et al. (Journal of Molecular Neuroscience, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Quantification of solute transport in a fracture-matrix system using geoelectrical monitoring - Yongshuai Yan; Jiazhong Qian; Lei Ma; Guizhang Zhao; Yaping Deng; Haoming Zhang; Yunhai Fang; Yong Liu (Journal of Hydrology, 2023)

Characterizing seasonal recharge between a river and shallow aquifer in a floodplain based on time-lapse electrical resistivity tomography - Yongshuai Yan; Yaping Deng; Lei Ma; Guizhang Zhao; Jiazhong Qian (Hydrogeology Journal, 2023)

Catalytic ozonation of phenol by ZnFe2O4/ZnNCN: performance and mechanism - Pengfei Yan; Yaping Ye; Mingwen Wang (Environmental Science and Pollution Research, 2022)

Hydrofacies simulation based on transition probability geostatistics using electrical resistivity tomography and borehole data - Lei Ma; Hui Deng; Yongshuai Yan; Yaping Deng; Weidong Zhao; Xiaohui Tan; Jiazhong Qian (Hydrogeology Journal, 2022)

Impact of green credit policy on sustainability performance of high-pollution enterprises - Yan Jiang; Shuyue Qin; Yaping Xu (Environmental Science and Pollution Research, 2022)

Vegetation dynamics and their relationships with climatic factors in the “Golden Triangle” region - Yaping Zhu; Juchao Zhao; Pifeng Lei; Kun Yang; Shaohua Zhang; Xiaoxue Yin; Yan Jiang (Environmental Science and Pollution Research, 2022)

A FRET Fluorescent Sensor for Ratiometric and Visual Detection of Sulfide Based on Carbon Dots and Silver Nanoclusters - Jing Yang; Yan Huang; Hanyue Cui; Li Li; Yaping Ding (Journal of Fluorescence, 2022)

A Significant Fluorescent Aptamer Sensor Based on Carbon Dots and Graphene Oxide for Highly Selective Detection of Progesterone - Hanyue Cui; Huan Lu; Jing Yang; Yao Fu; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2022)

Pandemic threat posed by H3N2 avian influenza virus - Yaping Zhang; Conghui Zhao; Yujie Hou; Yan Chen; Fei Meng; Yichao Zhuang; Liling Liu; Yasuo Suzuki; Jianzhong Shi; Guohua Deng; Hualan Chen (Science China Life Sciences, 2021)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Candidate gene analysis of watermelon stripe pattern locus ClSP ongoing recombination suppression - Zhen Yue; Rongxue Ma; Denghu Cheng; Xing Yan; Yaping He; Chunxia Wang; Xiaona Pan; Lijuan Yin; Xian Zhang; Chunhua Wei (Theoretical and Applied Genetics, 2021)

Proteomic analysis of the exosomes secreted from Ctenopharyngodon idellus kidney cells infected with grass carp reovirus reveals their involvement in the cellular responses to viral infection - Xing Zhang; Yunshan Zhang; Jun Pan; Min Zhu; Zi Liang; Zeen Shen; Kun Dai; Bingyu Yan; Yaping Dai; Renyu Xue; Guangli Cao; Xiaolong Hu; et al. (Fish Physiology and Biochemistry, 2021)

The influence of VDR polymorphisms on the type 2 diabetes susceptibility in Chinese: an interaction with hypertriglyceridemia - Dongdong Zhang; Cheng Cheng; Yan Wang; Yuan Xue; Yaping Liu; Yiming Liu; Mingming Feng; Ze Xu; Wenjie Li; Xing Li (Molecular Genetics and Genomics, 2021)

Conditional Deletion of Foxg1 Alleviates Demyelination and Facilitates Remyelination via the Wnt Signaling Pathway in Cuprizone-Induced Demyelinated Mice - Fuxing Dong; Dajin Liu; Feiyu Jiang; Yaping Liu; Xiuxiang Wu; Xuebin Qu; Jing Liu; Yan Chen; Hongbin Fan; Ruiqin Yao (Neuroscience Bulletin, 2021)
The massive loss of oligodendrocytes caused by various pathological factors is a basic feature of many demyelinating diseases of the central nervous system (CNS). Based on a variety of studies, it is now well established that impairment of oligodendrocyte precursor cells (OPCs) to differentiate and remyelinate axons is a vital event in the failed treatment of demyelinating diseases. Recent evidence suggests that Foxg1 is essential for the proliferation of certain precursors and inhibits premature neurogenesis during brain development. To date, very little attention has been paid to the role of Foxg1 in the proliferation and differentiation of OPCs in demyelinating diseases of the CNS. Here, for the first time, we examined the effects of Foxg1 on demyelination and remyelination in the brain using a cuprizone (CPZ)-induced mouse model. In this work, 7-week-old Foxg1 conditional knockout and wild-type (WT) mice were fed a diet containing 0.2% CPZ w/w for 5 weeks, after which CPZ was withdrawn to enable remyelination. Our results demonstrated that, compared with WT mice, Foxg1 -knockout mice exhibited not only alleviated demyelination but also accelerated remyelination of the demyelinated corpus callosum. Furthermore, we found that Foxg1 knockout decreased the proliferation of OPCs and accelerated their differentiation into mature oligodendrocytes both in vivo and in vitro . Wnt signaling plays a critical role in development and in a variety of diseases. GSK-3β, a key regulatory kinase in the Wnt pathway, regulates the ability of β-catenin to enter nuclei, where it activates the expression of Wnt target genes. We then used SB216763, a selective inhibitor of GSK-3β activity, to further demonstrate the regulatory mechanism by which Foxg1 affects OPCs in vitro . The results showed that SB216763 clearly inhibited the expression of GSK-3β, which abolished the effect of the proliferation and differentiation of OPCs caused by the knockdown of Foxg1 . These results suggest that Foxg1 is involved in the proliferation and differentiation of OPCs through the Wnt signaling pathway. The present experimental results are some of the first to suggest that Foxg1 is a new therapeutic target for the treatment of demyelinating diseases of the CNS.

Degradation of recalcitrant organic matter in SAARB leachate by a combined process of coagulation and catalytic ozonation - Yan Xiang; Yaping Chen; Siqiang Luo; Junliang Zou; Aiping Zhang (Environmental Science and Pollution Research, 2020)

Monoclonal Antibody-Based Treatments for Neuromyelitis Optica Spectrum Disorders: From Bench to Bedside - Wenli Zhu; Yaling Zhang; Zhen Wang; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2020)

Gene UCHL1 expresses specifically in mouse uterine decidual cells in response to estrogen - Lishuang Hao; Di Song; Mengfei Zhuang; Yan Shi; Lin Yu; Yaping He; Jian Wang; Tingting Zhang; Zhaogui Sun (Histochemistry and Cell Biology, 2020)

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

Myelin Oligodendrocyte Glycoprotein-IgG Contributes to Oligodendrocytopathy in the Presence of Complement, Distinct from Astrocytopathy Induced by AQP4-IgG - Ling Fang; Xinmei Kang; Zhen Wang; Shisi Wang; Jingqi Wang; Yifan Zhou; Chen Chen; Xiaobo Sun; Yaping Yan; Allan G. Kermode; Lisheng Peng; Wei Qiu (Neuroscience Bulletin, 2019)

Erratum to: Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2019)

Correlation of IL-31 gene polymorphisms with susceptibility and clinical recurrence of bladder cancer - Qin Li; Tielong Tang; Peng Zhang; Chenlu Liu; Yan Pu; Yan Zhang; Huizi Song; Yanyun Wang; Yaping Song; Min Su; Bin Zhou; Lin Zhang (Familial Cancer, 2018)

Molecular cytogenetic and genomic analyses reveal new insights into the origin of the wheat B genome - Wei Zhang; Mingyi Zhang; Xianwen Zhu; Yaping Cao; Qing Sun; Guojia Ma; Shiaoman Chao; Changhui Yan; Steven S. Xu; Xiwen Cai (Theoretical and Applied Genetics, 2018)

Association of genetic variations in RTN4 3′-UTR with risk for clear cell renal cell carcinoma - Yan Pu; Peng Chen; Bin Zhou; Peng Zhang; Yanyun Wang; Yaping Song; Lin Zhang (Familial Cancer, 2018)

LINGO-1-Fc-Transduced Neural Stem Cells Are Effective Therapy for Chronic Stage Experimental Autoimmune Encephalomyelitis - Xing Li; Yuan Zhang; Yaping Yan; Bogoljub Ciric; Cun-Gen Ma; Jeannie Chin; Mark Curtis; Abdolmohamad Rostami; Guang-Xian Zhang (Molecular Neurobiology, 2017)

Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2017)

Autoantibody to MOG suggests two distinct clinical subtypes of NMOSD - Yaping Yan; Yujing Li; Ying Fu; Li Yang; Lei Su; Kaibin Shi; Minshu Li; Qiang Liu; Aimee Borazanci; Yaou Liu; Yong He; Jeffrey L. Bennett; et al. (Science China Life Sciences, 2016)

Alterations of Synaptic Proteins in the Hippocampus of Mouse Offspring Induced by Developmental Lead Exposure - Haiyang Yu; Yingjun Liao; Tingting Li; Yan Cui; Gaoyang Wang; Fenghong Zhao; Yaping Jin (Molecular Neurobiology, 2016)

Environmental filtering decreases with fish development for the assembly of gut microbiota - Qingyun Yan; Jinjin Li; Yuhe Yu; Jianjun Wang; Zhili He; Joy D. Van Nostrand; Megan L. Kempher; Liyou Wu; Yaping Wang; Lanjie Liao; Xinghao Li; Shu Wu; et al. (Environmental Microbiology, 2016)
Summary Gut microbiota typically occupy habitats with definable limits/borders that are comparable to oceanic islands. The gut therefore can be regarded as an ‘island’ for the assembly of microbial communities within the ‘sea’ of surrounding environments. This study aims to reveal the ecological mechanisms that govern microbiota in the fish gut ‘island’ ecosystem. Taxonomic compositions, phylogenetic diversity, and community turnover across host development were analyzed via the high‐throughput sequencing of 16S rRNA gene amplicons. The results indicate that the Shannon diversity of gut microbiota in the three examined freshwater fish species all significantly decreased with host development, and the dominant bacterial taxa also changed significantly during host development. Null model and phylogenetic‐based mean nearest taxon distance (MNTD) analyses suggest that host gut environmental filtering led to the assembly of microbial communities in the fish gut ‘island’. However, the phylogenetic clustering of local communities and deterministic processes that governed community turnover became less distinct as the fish developed. The observed mechanisms that shaped fish gut microbiota seemed to be mainly shaped by the gut environment and by some other selective changes accompanying the host development process. These findings greatly enhance our understanding of stage‐specific community assembly patterns in the fish gut ecosystem.

The growth and reproduction performance of TALEN-mediated β-lactoglobulin-knockout bucks - Hengtao Ge; Chenchen Cui; Jun Liu; Yan Luo; Fusheng Quan; Yaping Jin; Yong Zhang (Transgenic Research, 2016)

NO is involved in spermidine-induced drought tolerance in white clover via activation of antioxidant enzymes and genes - Dandan Peng; Xiaojuan Wang; Zhou Li; Yan Zhang; Yan Peng; Yaping Li; Xiaoshuang He; Xinquan Zhang; Xiao Ma; Linkai Huang; Yanhong Yan (Protoplasma, 2016)

Neuroprotective Effect of Osthole on Neuron Synapses in an Alzheimer’s Disease Cell Model via Upregulation of MicroRNA-9 - Shaoheng Li; Yuhui Yan; Yanan Jiao; Zhong Gao; Yang Xia; Liang Kong; Yingjia Yao; Zhenyu Tao; Jie Song; Yaping Yan; Guangxian Zhang; Jingxian Yang (Journal of Molecular Neuroscience, 2016)

ace-3 plays an important role in phoxim resistance in Caenorhabditis elegans - Yan Han; Shaojuan Song; Yaping Guo; Jianzhen Zhang; Enbo Ma (Ecotoxicology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Experimental models of neuromyelitis optica: current status, challenges and future directions - Minshu Li; Yaping Yan (Neuroscience Bulletin, 2015)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

Development and characterization of 16 polymorphic microsatellite markers for the highly invasive ascidian, Ciona savignyi - Ping Ni; Yaping Lin; Yiyong Chen; Haitao Li; Yan Zhao; Aibin Zhan (Conservation Genetics Resources, 2015)

Trends of subtype variation of human immunodeficiency virus type 1 in Zhejiang Province, China - Yaping Yao; Ruolei Xin; Jiezhe Yang; Yun Xu; Jiafeng Zhang; Yan Xia; Xiaohong Pan; Zhihong Guo; Yanhui Song (Virus Genes, 2015)

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

A polymorphism at miRNA-122-binding site in the IL-1α 3′UTR is associated with risk of epithelial ovarian cancer - Zhu Zhang; Bin Zhou; Qianqian Gao; Yuke Wu; Kui Zhang; Yan Pu; Yaping Song; Lin Zhang; Mingrong Xi (Familial Cancer, 2014)

A PCR-based microwell-plate hybrid capture assay for high-risk human papillomavirus - Yumei Wang; Yan Liu; Yaping Ding; Nan Sun; Yafang Gong; Shangxian Gao (Archives of Virology, 2014)

Mutation screen and RNA analysis disclose the changed splicing of the E-cadherin transcription in gastric cancer - Xiaowei Li; Yafan Gao; Yiyuan Pan; Yan Pan; Lifeng Wang; Nong Xiao; Qiong He; Yimei Fan; Yaping Wang (Familial Cancer, 2013)

Anti-MS4a4B treatment abrogates MS4a4B-mediated protection in T cells and ameliorates experimental autoimmune encephalomyelitis - Yaping Yan; Zichen Li; Guang-Xian Zhang; Mark S. Williams; Gregory B. Carey; Jianke Zhang; Abdolmohamad Rostami; Hui Xu (Apoptosis, 2013)

Effect of chlorogenic acid on LPS-induced proinflammatory signaling in hepatic stellate cells - Haitao Shi; Lei Dong; Xiaoyan Dang; Yaping Liu; Jiong Jiang; Yan Wang; Xiaolan Lu; Xiaoyan Guo (Inflammation Research, 2013)

Geological events play a larger role than P leistocene climatic fluctuations in driving the genetic structure of Q uasipaa boulengeri ( A nura: D icroglossidae) - Fang Yan; Weiwei Zhou; Haitao Zhao; Zhiyong Yuan; Yunyu Wang; Ke Jiang; Jieqiong Jin; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Paleoclimatic and paleogeological events have been identified as being the two main drivers of genetic structuring in extant organisms. We used a montane stream‐dwelling frog, Q uasipaa boulengeri , to explore the relative roles played by these drivers on species in southern C hina, a region needing thorough studies. We detected four major matrilines, and no broadly distributed haplotypes occurred. The complex orogenesis of south‐western China drove matrilineal divergence in Q . boulengeri into highly structured geographical units. These matrilines subsequently persisted in situ with stable populations rather than undergoing expansions during glacial cycling. The unification of the upper and middle Y angtze R iver in the Three Gorges mountain region mediated downstream colonization of this frog. Analyses identified geological events as playing a larger role than climatic fluctuations in driving the population history of Q . boulengeri . Nuclear allele analyses indicated gene flow; this maintained genetic cohesion of the species. S outh‐eastern S ichuan B asin was identified as the area of secondary contact for several matrilines, and this area deserves further study and special protection.

River islands, refugia and genetic structuring in the endemic brown frog R ana kukunoris ( A nura, R anidae) of the Q inghai‐ T ibetan P lateau - Weiwei Zhou; Fang Yan; Jinzhong Fu; Shifang Wu; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Frequently, P leistocene climatic cycling has been found to be the diver of genetic structuring in populations, even in areas that did not have continental ice sheets, such as on the Q inghai‐ T ibetan P lateau ( QTP ). Typically, species distributed on the plateau have been hypothesized to re‐treat to south‐eastern refugia, especially during the L ast G lacial M aximum ( LGM ). We evaluated sequence variation in the mitochondrial DNA gene Cytb and the nuclear DNA gene RAG ‐1 in R ana kukunoris , a species endemic to the QTP . Two major lineages, N and S, were identified, and lineage N was further subdivided into N 1 and N 2. The geographical distribution and genealogical divergences supported the hypothesis of multiple refugia. However, major lineages and sublineages diverged prior to the LGM . Demographical expansion was detected only in lineage S and sublineage N 2. Sublineage N 1 might have survived several glacial cycles in situ and did not expand after the LGM because of the absence of suitable habitat; it survived in river islands. Genetic analysis and environment modelling suggested that the north‐eastern edge of QTP contained a major refugium for R . kukunoris . From here, lineage S dispersed southwards after the LGM . Two microrefugia in northern Q ilian M ountains greatly contributed to current level of intraspecific genetic diversity. These results were found to have important implications for the habitat conservation in N orthwest C hina.

Downregulation of Cinnamoyl CoA Reductase Affects Lignin and Phenolic Acids Biosynthesis in Salvia miltiorrhiza Bunge - Zhengjun Wang; Langjun Cui; Chen Chen; Xiaojing Liu; Yaping Yan; Zhezhi Wang (Plant Molecular Biology Reporter, 2012)

Distribution and dispersal pattern of clay minerals in surface sediments, eastern Beibu Gulf, South China Sea - Jun Li; Jianhua Gao; Yaping Wang; Yan Li; Fenglong Bai; Laban Cees (Acta Oceanologica Sinica, 2012)

Essential sequence of the N-terminal cytoplasmic localization-related domain of huntingtin and its effect on huntingtin aggregates - YaPing Yan; DanTao Peng; Jun Tian; JingWei Chi; JieQiong Tan; XinZhen Yin; JiaLi Pu; Kun Xia; BaoRong Zhang (Science China Life Sciences, 2011)

Effects of exogenous glutathione on arsenic burden and NO metabolism in brain of mice exposed to arsenite through drinking water - Yan Wang; Fenghong Zhao; Yaping Jin; Yuan Zhong; Xiaoyun Yu; Gexin Li; Xiuqiang Lv; Guifan Sun (Archives of Toxicology, 2011)

Znrg, a novel gene expressed mainly in the developing notochord of zebrafish - Yaping Zhou; Yan Xu; Jianzhen Li; Yao Liu; Zhe Zhang; Fengjiao Deng (Molecular Biology Reports, 2010)

Generation and analysis of expressed sequence tags from the medicinal plant Salvia miltiorrhiza - YaPing Yan; ZheZhi Wang; Wei Tian; ZhongMin Dong; David F. Spencer (Science China Life Sciences, 2010)

The application of geostatistics in grain size trend analysis: A case study of eastern Beibu Gulf - Fei Ma; Yaping Wang; Yan Li; Changjiang Ye; Zhiwei Xu; Fan Zhang (Journal of Geographical Sciences, 2010)

A quick isolation method for mutants with high lipid yield in oleaginous yeast - Jufang Wang; Renmin Li; Dong Lu; Shuang Ma; Yaping Yan; Wenjian Li (World Journal of Microbiology and Biotechnology, 2009)

Optimization of fermentation conditions for production of xylanase by a newly isolated strain, Penicillium thiersii ZH-19 - Fengjie Cui; Yin Li; Zhiqiang Liu; Hui Zhao; Lifeng Ping; Liying Ping; Yinan Yang; Yaping Xue; Lijiao Yan (World Journal of Microbiology and Biotechnology, 2009)

A Scheme for Scalar Exchange in the Urban Boundary Layer - Yan Yang; Yaping Shao (Boundary-Layer Meteorology, 2006)